Do more trucks lead to more motor vehicle fatalities in European roads? Evaluating the impact of specific safety strategies - Mercedes Castro-Nu\~no; José I. Castillo-Manzano; Xavier Fageda (European Regional Science Association (ERSA), 2015)
Truck operations have recently become an important focus of academic research not only because road freight transport is a key part of logistics, but because trucks are usually associated with negative externalities including pollution, congestion and traffic accidents. While the negative environmental impacts of truck activities have been extensively analyzed, comparatively little attention has been paid to the role of trucks in road accidents. A review of the literature identifies various truck-traffic safety related issues: frequency of accidents and their determinants; risk factors associated with truck driver behavior (including cell phone use, fatigue, alcohol and drugs consumption); truck characteristics and facilities (roadway types, specific lanes and electronic stability programs) to improve performance of vehicle maneuvering; and the safety characteristics of heavy and large trucks. However, to date, there seems to have been developed few studies evaluating the complex coexistence of trucks and cars on roads and that may support the implementation of differential road safety strategies applied to them. This paper focuses on the impact on the traffic fatalities rate of the interaction between trucks and cars on roads. We also assess the efficiency of two stricter road safety regulations for trucks, as yet not harmonized in the European Union; namely, speed limits and maximum blood alcohol concentration rates. For this, econometric models have been developed from a panel data set for European Union during the years 1999?2010. Our findings show that rising motorization rates for trucks lead to higher traffic fatalities, while rising motorization rates for cars do not. Furthermore, we also find that lower maximum speed limits for trucks are effective and maximum blood alcohol concentration rates for professional drivers are only effective when they are strictly set to zero. Therefore, our results point to that the differential treatment of trucks is not only adequate for mitigating an important source of congestion and pollution, but that the implementation of stricter road safety measures in European countries for the case of trucks also contributes significantly to reducing fatalities. In summary, and as a counterpoint to the negative impact of trucks on road traffic accidents, we conclude the effectiveness of efforts made in road safety policy (based on specific traffic regulations by vehicle type imposed by member States) to counteract the safety externalities of freight transportation in the European Union. In certain sense, our study might provide indirect support to public policies implemented at the macro European level to promote multimodal transport corridors. In this respect, there is an increasing focus at the European level on how freight transport can be moved from trucks on roads to more environmentally-sustainable modes, such as rail and ship.
Keywords: C23; I18; R41; 330; Trucks; Road Fatalities; Europe; Speed limits; Blood Alcohol Concentration